2016
DOI: 10.1007/s10552-016-0723-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake from early adulthood to midlife and mammographic density

Abstract: Purpose Moderate alcohol consumption (15 grams/day) has been consistently associated with increased breast cancer risk; however, the association between alcohol and mammographic density, a strong marker of breast cancer risk, has been less consistent. Less is known about the effect of patterns of alcohol intake across the lifecourse. Methods Using the Early Determinants of Mammographic Density study, an adult follow-up of women born in two US birth cohorts (N=697; Collaborative Perinatal Project in Boston an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The EDMD study is an adult follow-up of women born in 2 US birth cohorts: the CHDS cohort, which was enrolled in California between 1959 and1967 (44, 50), and 2 sites of the NCPP enrolled in Boston, Massachusetts, and Providence, Rhode Island, between 1959 and 1966 (45). Details of this cohort have been published previously (46)(47)(48)(49). Briefly, we attempted to contact 1,925 women randomly selected from the 3,256 eligible women.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDMD study is an adult follow-up of women born in 2 US birth cohorts: the CHDS cohort, which was enrolled in California between 1959 and1967 (44, 50), and 2 sites of the NCPP enrolled in Boston, Massachusetts, and Providence, Rhode Island, between 1959 and 1966 (45). Details of this cohort have been published previously (46)(47)(48)(49). Briefly, we attempted to contact 1,925 women randomly selected from the 3,256 eligible women.…”
Section: Study Populationmentioning
confidence: 99%
“…We recently conducted a study examining prospective measurements of infant weight gain and MD in an urban birth cohort and found negative associations between infant and early childhood weight gain and MD (43). However, given the smaller sample size and the lack of siblings in this cohort, we undertook a prospective study of MD in women of a similar age nested within the Child Health and Development Studies (CHDS) cohort (44) and the National Collaborative Perinatal Project (NCPP) (45), the Early Determinants of Mammographic Density (EDMD) study (46)(47)(48)(49). EDMD is a larger study population with prospectively measured infant and childhood weight and height that includes a subgroup of siblings.…”
mentioning
confidence: 99%
“…In both absolute and relative models of change, we adjusted for baseline density, which is strongly affected by demographic characteristics and premenopausal risk factors; therefore, it is possible that these factors have no effect on change in breast density aside from their effect on the premenopausal density. Interestingly, we found that alcohol had a strong effect on premenopausal DV, showing an increasing DV with increasing levels of alcohol use, although previous literature using area-based density has been mixed (18)(19)(20).…”
Section: Discussionmentioning
confidence: 56%
“…Among premenopausal women in the Norwegian Energy Balance and Breast Cancer Aspects Study, women who reported weekly alcohol consumption of at least 7 drinks (20%) had higher percent density and absolute dense area than women who consumed <1 drink/week [23]. In contrast, drinking was significantly inversely associated with MD in two US birth cohorts [28]. In that study, 12.8% of women reported weekly consumption of >7 alcoholic drinks during the past year.…”
Section: Discussionmentioning
confidence: 99%
“…This current analysis of premenopausal NHS II participants showed similarities in percent MD, absolute dense breast area, and non-dense breast area between women with alcohol consumption of ≥10 g/day prior to first pregnancy and non-drinkers before first pregnancy. Five studies have evaluated alcohol drinking during early life and MD [23, 25, 27, 28, 31], with the majority reporting no association after adjustment for established breast cancer risk factors. The Energy Balance and Breast Cancer Aspects Study assessed alcohol consumption among 202 premenopausal women from age 15 through the time of interview when the average age was 30 years [23].…”
Section: Discussionmentioning
confidence: 99%